Experimental evaluation of the effects of ballistic impact on laminated glass - Laguda, Ronnie C. (2006)
Vision blocks made of laminated glass used in armored vehicles of the Armed Forces of the Philippines are very expensive and take longer lead time to import from foreign countries. An optimized design of vision blocks for local production was tested. Laminated glass interleaved with thin layers of polymer was subjected to ballistic penetration. Initial experiments were first performed on laminated glass of different thicknesses and number of layers without interleaving polymers between the glass panes. This was done to determine the best laminated glass configuration that can best offer higher resistance against ballistic penetration. The spall cloud area, energy absorbed and residual depths of penetration were then measured to determine the resistance offered by each type of laminated glass structure to ballistic penetration. Two types of polymer materials were then embedded in between the glass layers to further increase the resistance of the substrate. Results showed that the best configuration of laminated glass using resistance to ballistic penetration, energy absorbed and production cost as parameters is the 4-layer glass laminate and that the 21M security film polymer material was proven to have increased the ballistic resistance of the laminated glass much higher than the sentryglas polymer material.